From single variants to protein cascades: multiscale modeling of single nucleotide variant sets in genetic disorders - Müller, Sabine C.; Haas, Jan; Meder, Benjamin (The journal of biological chemistry, 2016)
Sabine C. Mueller, Björn Sommer, Christina Backes, Jan Haas, Benjamin Meder, Eckart Meese, Andreas Keller